Высокодобротные резонаторные нерегулярные структуры - Близнюк, И. Ю.; Бондаренко, И. Н. (ХНУРЕ, 2019)
The possibilities and conditions for the creation of high-quality microwave resonance devices based on irregular and hybrid bulk structures are considered. Theoretical numerical model investigations are produced. The possibility of achieving high values of quality is shown.
Keywords: Резонаторные структуры